Genetic Interaction Between Site-Specific Epigenetic Marks and Roles of H4v in Transcription Termination in Trypanosoma brucei - Kim, Hee-Sook (Frontiers in Cell and Developmental Biology, 2021)
In Trypanosoma brucei, genes are assembled in Polycistronic Transcription Units (PTUs). Boundaries of PTUs are designated Transcription Start Sites (TSSs) and Transcription Termination Sites (TTSs). Messenger RNAs are generated by trans-splicing and polyadenylation of precursor RNAs, and regulatory information in the 3´ UTR, rather than promoter activity/sequence-specific transcription factors, controls mRNA levels. Given this peculiar genome structure, special strategies must be utilized to control transcription in T. brucei. TTSs are deposition sites for three non-essential chromatin factors – two of non-canonical histone variants (H3v, H4v) and a DNA modification (base J, which is a hydroxyl-glucosyl dT). This association generated the hypothesis that these three chromatin marks define a transcription termination site in T. brucei. Using a panel of null mutants lacking H3v, H4v, and base J, here I show that H4v is a major sign for transcription termination at TTSs. While having a secondary function at TTSs, H3v is important for monoallelic transcription of telomeric antigen genes. The simultaneous absence of both histone variants leads to proliferation and replication defects, which are exacerbated by the J absence, accompanied by accumulation of sub-G1 population. Thus, I propose that the coordinated actions of H3v, H4v and J provide compensatory mechanisms for each other in chromatin organization, transcription, replication, and cell-cycle progression.